Eliza Haywood’s empathy: creating a narrative discourse of her own - Lutsenko, Lyudmyla (Penerbit Universiti Kebangsaan Malaysia, 2018)
Based on Suzanne Keen’s theory of narrative empathy, this article shows a variety of narrative techniques employed by the famous eighteenth century English woman writer, Eliza Haywood, in the amatory novel of intrigue “Idalia, Or, The Unfortunate Mistress” (1723) to evoke the reader’s empathy. They include character identification, an excessive conflict paradigm, narrative voice, focalization as well as the narrator’s intrusion, known in narratology as metallepsis. The narrative analysis leads to the conclusion that from the addresseeorientated perspective the author creates an ambassadorial emphatic discourse that enables her to communicate thoughts to other members of the women’s community with a view to involving them in the experience of the main character who is vulnerable to sexual desire and betrayal. By doing so, Haywood pursues the goals of not only exercising women readers in “fellow- feeling” but acquiring knowledge about themselves through empathizing, and influencing attitudes to a woman’s limited role in society as well.